HISTORY OF THE MILITARY ART OF THE PEOPLES OF THE ANCIENT WORLD - Qarshiyev Azamat Rahmonovich (Journals Park Publishing, 2024)
In this article, the History of Military Art of the Peoples of the Ancient World was the oldest classified societies in human history: Egypt, Syria, Iran, India, and China. This article is intended for familiarization with students of higher and secondary specialized institutions.
Keywords: Gomer's